Global status and emerging contribution of other effective area-based conservation measures (OECMs) towards the ‘30x30’ biodiversity Target 3 - Jonas, Harry D.; Bingham, Heather C.; Bennett, Nathan J.; Woodley, Stephen; Zlatanova, Ryan; Howland, Emily; Belle, Elise; Upton, Jasmin; Gottlieb, Bex; Kamath, Vignesh; Lessmann, Janeth; Delli, Giacomo; et al. (Frontiers in Conservation Science, 2024)
Other effective area-based conservation measures (OECMs) are sites outside of protected areas that deliver the effective, long-term conservation of biodiversity. Both protected areas and OECMs contribute to the implementation of the Global Biodiversity Framework’s Target 3, which calls for the conservation of 30% of marine, terrestrial and inland water areas by 2030. This paper provides the first global assessment of the contribution of OECMs to GBF Target 3. Between 2019 and 2023, 820 sites in nine countries and territories were reported to the World Database on OECMs, covering 1.9 million km2 of the Earth’s surface and, in the terrestrial realm, contributing over 1% to the 30% coverage target. Notably, over 50% of reported OECMs are under governance by governments and less than 2% are governed by Indigenous peoples and local communities. In countries and territories that have reported OECMs, a far greater proportion of OECMs than protected areas are under shared governance (40.9% compared to 2.5%), and collaborative governance is the most common governance sub-type among reported OECMs. This paper finds that almost 30% of the 820 reported OECMs overlap with identified Key Biodiversity Areas, which are one global classification of areas of particular importance for biodiversity. With Target 3’s pressing deadline of 2030, there is an urgent need to scale up understanding and local to national engagement with the OECM framework, ensuring that it fulfills its potential to recognize diverse forms of equitable governance and effective conservation.